Effects of feeding Candida utilis-fermented pea starch on overall, metabolic and intestinal health of dogs and cats - Curso-Almeida, Priscilla; Subramaniam, Marina; Costa, Matheus de Oliveira; Adolphe, Jennifer L.; Drew, Murray D.; Loewen, Matthew E.; Weber, Lynn P. (Frontiers in Veterinary Science, 2025)
Pulse-based pet foods often contain peas or pea starch, which tend to impart a bitter taste. Fermentation increases feed palatability, but also has the potential to improve overall health. Therefore, the current study used the yeast, Candida utilis, to ferment pea starch for use in pet food and assessed health effects, focusing on metabolic and intestinal health in dogs and cats. Whole diets had ~30% starch inclusion of either C. utilis-fermented pea starch, unfermented pea starch, or a control corn diet fed over a 20-day period to beagle dogs and domestic cats. Complete blood count, biochemistry, adipokines, and triglyceride levels were assessed, along with fecal short chain fatty acids, microbial diversity and abundance to measure intestinal health. It was found that pea-based diets (regardless of fermentation) generally resulted in improved metabolic health by both species, indicated by lower plasma triglycerides, cholesterol, and leptin levels compared to the control corn diet. Additionally, the C. utilis-fermented pea starch diet improved dog fecal microbial diversity, while both pea diets increased richness and evenness in the microbial population and a larger Faecalibacterium population compared to dogs fed the corn-based diet. In contrast, cat microbiome could not be quantitatively evaluated due to poor fecal quality. Taken together, inclusion of pea starch improves metabolic and intestinal health after 20 days consumption in dogs, while fermentation of pea starch with C. utilis may provide additional benefit.